Descriptive Analysis Performance Analysis, Satisfaction Level and Program Achievement Based on Leadership Profession Head of Public Health Center Throughout Banyuwangi District 2018 - Purwaningsih, Henny; Siyoto, Sandu; Koesnadi (Journal for Research in Public Health, 2020)
Health management is an activity or an art to regulate health workers and non-public health officers through health programs. One of the objectives of managing human resources in organizational management functions is related to leadership problems. Someone who has been appointed as a leader to lead his subordinates, he must carry out the function of the organization itself which determines the success or failure of a company. The purpose of the study was to analyze the descriptive performance, level of satisfaction and achievement of the program based on the professional leadership of the head of the Public health throughout Banyuwangi District. The research design used was cross sectional. The population of the study was all heads of administration of Public health throughout Banyuwangi District and the sample size was 45 people using total sampling. Data collection using sheets and questionnaires was then analyzed using the Friedman test. The results showed that the profession of physician leadership most of the performance of high category as many as 17 respondents (70.8%), and professional leadership performance Bachelor of Public Health mostly high category, a total of 18 respondents (85.7%), physician leadership professions most levels of satisfaction satisfied category as many as 20 respondents (83.3%) , and the Bachelor of Public Health leadership profession were mostly satisfied category performance, namely as many as 17 respondents (81.0%) and the leadership profession the majority of the doctor's program achievements and Bachelor of Public Health good categories were as much as 100%. Based on this research, he can improve his skills and professionalism at work